2014
DOI: 10.1245/s10434-014-3735-1
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy for Extremity Soft Tissue Sarcoma: In the Absence of a Clear Survival Benefit, Why Do We Give It?

Abstract: Due in large part to several sentinel contributions from the National Cancer Institute (NCI), the local management of extremity soft tissue sarcoma (ESTS) today typically results in excellent local control and very good limb function. In 1982, Rosenberg et al. 1 showed equivalent 5-year survival rates for limb-sparing surgery (LSS) plus radiation therapy (RT) compared with amputation and an acceptable 15 % local recurrence (LR) rate for LSS plus RT. Following publication of this landmark trial, amputation rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…8 These conflicting data have raised questions of whether the benefit of treating patients with high-grade STS with radiation therapy is simply to reduce the risk of LR or whether it also may increase the likelihood of long-term survival. 9 Moreover, given the potential complications associated with radiation therapy, if radiation therapy does not improve survival, then it perhaps it should be omitted in select sarcoma patients. Indeed, several studies have shown that, in selected patients, appropriate surgery alone can achieve adequate local control and survival, while avoiding the morbidity of radiation therapy.…”
mentioning
confidence: 99%
“…8 These conflicting data have raised questions of whether the benefit of treating patients with high-grade STS with radiation therapy is simply to reduce the risk of LR or whether it also may increase the likelihood of long-term survival. 9 Moreover, given the potential complications associated with radiation therapy, if radiation therapy does not improve survival, then it perhaps it should be omitted in select sarcoma patients. Indeed, several studies have shown that, in selected patients, appropriate surgery alone can achieve adequate local control and survival, while avoiding the morbidity of radiation therapy.…”
mentioning
confidence: 99%
“…Margin‐negative resection for extremity sarcoma has been demonstrated to be an important prognostic factor from this disease 20‐22 in addition to size 23 histology, and grade 24,25 . The addition of radiation has been previously shown to improve the likelihood of margin‐negative resection this has not consistently translated to a survival benefit 8,14,26 . NAR improved margin‐negative resection however this did not translate to improved survival over AR or surgery alone.…”
Section: Discussionmentioning
confidence: 99%
“…Key studies have demonstrated that the addition of RT improves margin‐negative resection rates and local control for this disease 5,7,12 . Although these improvements have not translated to a survival benefit in most studies, the benefit of radiation in the treatment of extremity sarcomas is well‐established 13,14 . The timing of delivery remains a significant area of study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No randomized study has specifically defined the subgroup of patients with high‐grade tumors who do not require RT. Given the conflicting outcomes of nonrandomized trials and the clear benefit in local control that is offered by adjuvant RT in randomized trials, the standard treatment for most high‐grade lesions remains limb preservation surgery that is followed by RT 64 …”
Section: Management Of Local/localized Disease (See Figure 1)mentioning
confidence: 99%